John James Audubon [videorecording (DVD)] : drawn from nature (American masters (Television program), 2016)
John James Audubon's story is dramatic and surprising. He was not born in America, but saw more of the North American continent than virtually anyone alive. His growing apprehension about the destruction of nature became his prophecy. As an artist and naturalist his achievements were monumental. John James Audubon: Drawn from Nature creates a meaningful portrait of Art and Science in the first decades of the 19th century.